Association between glycemic variability and all-cause mortality in critically ill patients with non-traumatic subarachnoid hemorrhage: a retrospective study based on the MIMIC-IV database - Yuyang Hou; Xinyi Guo; Jiasheng Yu (European Journal of Medical Research)
Abstract Background Abnormal glycemic variability (GV), defined as acute fluctuations in blood glucose, is a prevalent phenomenon observed in critically ill patients and has been linked to unfavorable outcomes, including elevated mortality. However, the impact of this factor on patients with non-traumatic subarachnoid hemorrhage (SAH) remains unclear. The aim of this study is to explore the relationship between GV and all-cause mortality (ACM) in patients with non-traumatic SAH. Methods All blood glucose measurements taken within the initial 72-h period following intensive care unit (ICU) admission for non-traumatic SAH patients were extracted. The coefficient of variation (CV) was employed to quantify GV, defined as the ratio of the standard deviation (SD) to the mean blood glucose. Patients were stratified into tertiles based on their GV. Furthermore, we assessed ACM at multiple timepoints, including at ICU, in-hospital, 30 days, 90 days, 180 days, and 1 year. The relationship between GV and ACM was analyzed using Cox proportional hazards regression models and restricted cubic splines (RCS). Kaplan–Meier survival curves were used to estimate survival across different GV groups. Subgroup analyses were performed to evaluate the robustness of the findings. Results The study cohort comprised a total of 1056 patients, of whom 55.6% were female. The mortality rates observed in the ICU, hospital, and at various timepoints, including 30 days, 90 days, 180 days, and 1 year, were 12.8%, 16.2%, 17.5%, 21.5%, 24.3%, and 26.6%, respectively. Multivariate Cox regression analysis revealed a significant association between the high GV (≥ 20.4%) and ACM among patients with SAH. RCS analysis revealed a nonlinear U-shaped correlation between GV and ACM. Conclusions GV was identified as an independent risk factor for ACM in critically ill patients with non-traumatic SAH. These findings indicate that enhancing GV stability could potentially contribute to reducing mortality rates among non-traumatic SAH patients.